2015
DOI: 10.5154/r.rchscfa.2014.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Modelado de cambios de cobertura y uso del suelo: escenarios prospectivos en el Estado de México. Estudio de caso Amanalco de Becerra

Abstract: T he aim of this study is to assess the dynamics and processes of change that have occurred in the municipality of Amanalco de Becerra, State of Mexico, through the construction of a spatially explanatory model of land use/cover changes (LUCC). The modeling process was carried out using DINAMICA EGO, a mapping tool. Land use/cover maps for the years 1989, 1997 and 2009, as well as various explanatory physical-geographical, environmental and land tenure proximity variables, were used as map inputs. The LUCC for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…This reduction in native vegetal cover is not exclusive from our study region; it is rather a worldwide pattern [6] that has increased in recent years in NPAs and different areas from other countries [8, 9,62,63]. Although the causes of these changes were not assessed in this work, recent studies on LULCC [12,25,26] that include the evaluation of NPAs [27,28] and their surrounding areas [31] have shown that deforestation due to overexploitation, uncontrolled logging, agricultural activities, consumer demand, fires, pests, and urban growth, as well as natural phenomena arising from climate change, are some of the main factors that influence the loss of vegetation in Mexico [2]. In other areas, the increase in land cover changes has been caused by the rapid population growth, the multiplication of human settlements, and regional economic development [8- 10,64].…”
Section: Land Use-cover Changes Within the Natural Protected Area Altmentioning
confidence: 80%
“…This reduction in native vegetal cover is not exclusive from our study region; it is rather a worldwide pattern [6] that has increased in recent years in NPAs and different areas from other countries [8, 9,62,63]. Although the causes of these changes were not assessed in this work, recent studies on LULCC [12,25,26] that include the evaluation of NPAs [27,28] and their surrounding areas [31] have shown that deforestation due to overexploitation, uncontrolled logging, agricultural activities, consumer demand, fires, pests, and urban growth, as well as natural phenomena arising from climate change, are some of the main factors that influence the loss of vegetation in Mexico [2]. In other areas, the increase in land cover changes has been caused by the rapid population growth, the multiplication of human settlements, and regional economic development [8- 10,64].…”
Section: Land Use-cover Changes Within the Natural Protected Area Altmentioning
confidence: 80%
“…By using the WoE values of the variables used in the analysis of LULCC, the Dinamica-EGO model calculates the transition probability of each pixel to change. Thus, the pixels are assigned with a probability value for a given transition and probability maps are generated for the transitions of interest (Soares-Filho, Rodrigues & Costa, 2009; Soares-Filho et al., 2010; Mas & Flamenco, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…By using the WoE values of the variables used in the analysis of LULCC, the Dinamica-EGO model calculates the transition probability of each pixel to change. Thus, the pixels are assigned with a probability value for a given transition and probability maps are generated for the transitions of interest Mas and Flamenco, 2011).…”
Section: Selection Of Variables and Transitionsmentioning
confidence: 99%
“…The validation was carried out based on the FSI, as it was also performed in previous research (Ximenes et al, 2011). The result of this analysis, where the three aforementioned methods are combined, highlighted the variables driving the process of degradation/deforestation, as well as the manipulation based on the knowledge of the transition probabilities, being more suitable for the simulation of LULCC (Mas & Flamenco, 2011). The transition probability matrices revealed that the primary forest has a negative trend in its occupied area, suggestsing that degradation will continue over this land use, this area of primary forest changed to secondary forest.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%